Survey of Leading Commodities Of Aceh Province As Academic Effort To Join And Build The Country - Nur Ilham, Rico; Heikal, Mohd.; Khaddafi, Muammar; F, Falahuddin; Ichsan, Ichsan; F, Fuadi; Abbas, Damanhur; Fauzul Hakim Hasibuan, Ahmad; Munandar, Munandar; Chalirafi, Chalirafi (RADJA PUBLIKA, 2021)
Local governments must be able to prioritize superior commodities which are considered as the basis for sub-sectors to optimize regional economic advantages. Understanding the priorities of development planning and commodities in the agricultural, plantation and livestock sub-sectors in Aceh Province, it is necessary to know which agricultural, plantation and livestock sub-sectors are the leading and leading commodities in the agricultural, plantation and livestock sectors in Aceh Province. This research for community service was carried out on September 25, 2020 - August 25, 2021 with the location survey method. The criteria used based on this survey are 7 leading commodities in Aceh Province which include red chilies, cayenne peppers, shallots, beef, chicken meat, rice and eggs. The results of this service show that the agriculture and plantation sub-sectors are superior commodities from the period September 2020 - August 2021 with 9 regional locations in Aceh Province. Likewise with the nominated livestock sub-sector as a superior commodity in Aceh Province.